Deep renovation of historic buildings: The IEA-SHC Task 59 path towards the lowest possible energy demand and CO2 emissions. Issue 4 (4th October 2019) - Herrera-Avellanosa, Daniel; Haas, Franziska; Leijonhufvud, Gustaf; Brostrom, Tor; Buda, Alessia; Pracchi, Valeria; Webb, Amanda Laurel; Hüttler, Walter; Troi, Alexandra
Abstract : Purpose: Improving the energy performance of historic buildings has the potential to reduce carbon emissions while protecting built heritage through its continued use. However, implementing energy retrofits in these buildings faces social, economic, and technical barriers. The purpose of this conceptual paper is to present the approach of IEA-SHC Task 59 to address some of these barriers. Design/methodology/approach: Task 59 aims to achieve the lowest possible energy demand for historic buildings. This paper proposes a definition for this concept and identifies three key socio-technical barriers to achieving this goal: the decision-makers' lack of engagement in the renovation of historic buildings, a lack of support during the design process and limited access to proven retrofit solutions. Two methods – dissemination of best-practice and guidelines – are discussed in this paper as critical approaches for addressing the first two barriers. Findings: An assessment of existing databases indicates a lack of best-practice examples focused specifically on historic buildings and the need for tailored information describing these case studies. Similarly, an initial evaluation of guidelines highlighted the need for process-oriented guidance and its evaluation in practice. Originality/value: This paper provides a novel definition of lowest possible energy demand for historic buildings that is broadly applicable in both practice and research. Both best-practices and guidelines are intended to be widely disseminated throughout the field.